Sorting It Out: Contribution-Action Gap in Waste Segregation in Urban India - Ahana Basistha; Nishith Prakash; Raisa Sherif (Institute of Labor Economics (IZA), 2024)
Urban waste management challenges pose significant health and economic consequences. Although source-level waste segregation offers a promising solution, its success depends on household participation. Through a randomized controlled trial in the capital city of Bihar, India, we evaluate how light-touch messaging interventions influence household waste management practices. Our results reveal a stark behavioral disconnect: while interventions increased financial contributions to waste segregation initiativesby 9.6 - 11.7 percent compared to the control group, they failed to improve actual waste segregation practices. This gap between financial support and behavioral change highlights the complexity of promoting sustainable waste management practices in urban households.
Keywords: D01; D91; C93; Q53; O13; 330; willingness to contribute; household waste management; religious messaging; civic messaging; waste segregation; field experiment; India